Evaluate the Effectiveness of Various Interventions and their impact on Functional Independence (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Background Depending on the cause and the site of anatomical damage, hemorrhage may havea wide variety of clinical presentations. It's a very frequent but potentially life-threatening medical issuethat needs prompt attention. The function of the interprofessional team in enhancing treatment for patientswith hemorrhage is highlighted in this learning exercise. The research was conducted to learn howinformal caregivers' care burden and quality of life were affected by their charges' functional state after aHemorrhage. Aim The aim of this study is to analyze the effect of task-oriented intervention on thefunctional independence of people who have had a hemorrhage. Methods The data was evaluated andstatistically analyzed using the SPSS 15.0 package application. For counted variables, descriptivestatistics were presented as counts and percentages, whereas for measured variables, they werepresented as means, standard deviations, medians, and minimums and maximums. Caregiver burdenand quality of life were evaluated using the Caregiver Burden Scale (CBS) and the Short-Form HealthSurvey Quality of Life Scale, while demographic information was gathered using the Patient andCaregiver Information Form. Results The main findings of the research showed that all eight FIMsubscales showed improvement, with seven of them showing statistically significant improvement. Theonly clinical characteristic associated with a statistically significant degree of correlation with functionalindependence among hemorrhage patients was bleeding duration (p